2012
DOI: 10.1038/bmt.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous PBSC transplantation for poor prognosis germ cell tumors: a retrospective monocenter analysis of 44 cases

Abstract: Germ cell cancer (GCC) is curable in metastatic stages. The International Germ Cell Cancer Collaborative Group (IGCCCG) reports a poor prognosis subgroup with a 5-year survival of 48%. High-dose chemotherapy with PBSC transplantation (HD-PBSCT) in these patients showed promising results in phase II, but failed to show significant advantage in randomized trials. We report our monocenter series of all poor and selected intermediate prognosis germ cell tumor patients treated with multiple-course HD-PBSCT and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…demonstrated that the CR, PR and refractory disease rates in patients with GCTs in the intermediate or poor-risk groups, as defined by the IGCCCG, were approximately 50%, 36% and 14%, respectively. 14 Contrarily, Vaena et al. reported lower response rates with higher mortality rates for the GCT patients in the intermediate or poor-risk groups.…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that the CR, PR and refractory disease rates in patients with GCTs in the intermediate or poor-risk groups, as defined by the IGCCCG, were approximately 50%, 36% and 14%, respectively. 14 Contrarily, Vaena et al. reported lower response rates with higher mortality rates for the GCT patients in the intermediate or poor-risk groups.…”
Section: Discussionmentioning
confidence: 98%
“…According to the literature, most of the studies consist nonhomogenous groups like our study. Mohr M et al presented in a retrospective analysis of patients with poor or intermediate prognostic factors according to the IGCCCG with GCT CR, PR, and refractory disease were approximately 50%, 35%, and 15%, respectively (15). Additionally, Vaena et al reported lower response rates with higher mortality rates (8).…”
Section: Discussionmentioning
confidence: 99%
“…It can be performed as a first-line, second-line therapy or it can be an alternative therapy in heavily treated refractory patients. Although high-survival rates (more than 70%) were documented in the literature when ASCT was performed as first-line therapy in patients with poor prognostic factors (14), the role of ASCT as a first-line treatment in patients with poor prognostic markers is not clear. The International Prognostic Factors Study Group offered data of 1594 patients with GCT, who have progressed after at least three cycles of cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…PR was defined as PET/CT of the disease with an evidence of response. PR was divided into PR with negative tumor markers (tumor markers within normal range) and PR with positive tumor markers (high tumor marker levels) (14). Progressive disease (PD) was accepted as more than 25% increase in PET/ CT measurable mass or more than 10% increase of elevated tumor markers.…”
Section: Response Evaluationmentioning
confidence: 99%